2014
DOI: 10.1136/gutjnl-2014-307883
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between infliximab concentrations, antibodies to infliximab and disease activity in Crohn's disease

Abstract: ObjectiveAlthough low infliximab trough concentrations and antibodies to infliximab (ATI) are associated with poor outcomes in patients with Crohn's disease (CD), the clinical relevance of ATI in patients with adequate infliximab concentrations is uncertain. We evaluated this question using an assay sensitive for identification of ATI in the presence of infliximab.DesignIn an observational study, 1487 trough serum samples from 483 patients with CD who participated in four clinical studies of maintenance inflix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
172
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 251 publications
(189 citation statements)
references
References 37 publications
(40 reference statements)
6
172
1
4
Order By: Relevance
“…The same author performed another study in 483 adult patients in which the cut-off was calculated as 2.7 µg/mL using CRP level ≤5 mg/L as a marker of remission. In a prospective randomised controlled trial, target doses of 3-7 µg/mL were recommended; however, after dose optimization, continued concentration-based dosing was not superior to clinically based dosing [28]. …”
Section: Discussionmentioning
confidence: 99%
“…The same author performed another study in 483 adult patients in which the cut-off was calculated as 2.7 µg/mL using CRP level ≤5 mg/L as a marker of remission. In a prospective randomised controlled trial, target doses of 3-7 µg/mL were recommended; however, after dose optimization, continued concentration-based dosing was not superior to clinically based dosing [28]. …”
Section: Discussionmentioning
confidence: 99%
“…If the share was ≥ 3 the sample was positive for ATIs. IFX TL ≥ 2.8 μg/ml was considered to be therapeutic concentration of the drug during maintenance therapy in this study [10] .…”
Section: Measurement Of Pharmacokinetic Parametersmentioning
confidence: 99%
“…Using the homogeneous mobility shift assay (HMSA), Vande Casteele et al [52] demonstrated either an IFX concentration of [2.79 lg/ml or an ATI concentration of \3.15 U/ml was associated with remission; multivariable analysis indicated that concentrations of ATI and IFX were independent predictors of remission. HMSA, first developed by Wang et al [53], allows the detection of ATI in the presence of IFX, thereby overcoming the limitations of the ELISA method, which can only measure ATI in the absence of IFX because IFX interferes with the assay [54].…”
Section: Biomarkers Predicting Therapeutic Efficacymentioning
confidence: 97%